Perinatal asphyxia and Alzheimer's disease: is there a correlation? - Arruda, Bruna Petrucelli; Martins, Pamela Pinheiro; Kihara, Alexandre Hiroaki; Takada, Silvia Honda (Frontiers in Pediatrics, 2025)
The perinatal development period is critical for the formation of brain structures responsible for cognitive functions. Disruptions during this phase, such as perinatal asphyxia, characterized by impaired gas exchange and hypoxia, can lead to long-lasting neuronal damage and increased susceptibility to neurodegenerative diseases, including Alzheimer's disease (AD). AD, the most common cause of dementia globally, is marked by amyloid plaques, neurofibrillary tangles, and progressive cognitive decline. Emerging evidence links perinatal asphyxia with an elevated risk of AD, highlighting the potential role of oxidative stress, neuroinflammation, and epigenetic modifications as mediators. This review explores the mechanisms underlying brain damage after perinatal asphyxia, emphasizing oxidative stress, inflammation, and epigenetic changes that contribute to lifelong neurodegenerative susceptibility. Additionally, biomarkers identified in animal models reveal parallels between perinatal asphyxia and AD pathology, such as amyloid precursor protein alterations, gliosis, and microglial activation. These findings suggest perinatal asphyxia may prime microglia and epigenetically alter gene expression, predisposing individuals to chronic neurodegeneration. Future research should leverage advanced methodologies, including transcriptomics, epigenomics, and aged brain organoid models, to elucidate early-life influences on AD development. Understanding these mechanisms may pave the way for novel prevention strategies targeting early-life risk factors for neurodegenerative diseases.